1997
DOI: 10.1104/pp.115.1.249
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and Calmodulin Dynamics during Photopolarization in Fucus serratus Zygotes

Abstract: l h e role of CaZ+ in zygote polarization in fucoid algae (Fucus, Ascophyllum, and Pelvetia species) zygote polarization i s controversial. Using a local source of Fucus serratus, we established that zygotes form a polar axis relative to unilateral light (photopolarization) between 8 and 14 h after fertilization (AF), and become committed t o this polarity at approximately 15 to 18 h AF. We investigated the role of Caz+, calmodulin, and actin during photopolarization by simultaneously exposing F. serratus zygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 55 publications
(80 reference statements)
2
33
1
Order By: Relevance
“…The Ca 2ϩ signal at the rhizoid apex is essential for turgor and volume regulation (13) and probably involves the regulation of ion channels that allow osmoregulatory ion efflux (24). Polarized growth requires localized Ca 2ϩ elevation, transduced via Ca 2ϩ ͞calmodulin (25,26), regulation of targeted exocytosis (27), and a functional cytoskeleton (28). Studies with the Mn 2ϩ quench technique revealed a role for Ca 2ϩ influx in the generation of Ca 2ϩ signals in the rhizoid apex (13).…”
Section: Resultsmentioning
confidence: 99%
“…The Ca 2ϩ signal at the rhizoid apex is essential for turgor and volume regulation (13) and probably involves the regulation of ion channels that allow osmoregulatory ion efflux (24). Polarized growth requires localized Ca 2ϩ elevation, transduced via Ca 2ϩ ͞calmodulin (25,26), regulation of targeted exocytosis (27), and a functional cytoskeleton (28). Studies with the Mn 2ϩ quench technique revealed a role for Ca 2ϩ influx in the generation of Ca 2ϩ signals in the rhizoid apex (13).…”
Section: Resultsmentioning
confidence: 99%
“…Latrunculin A affects actin polymerization in a manner consistent with the formation of a 1:1 latrunculin-G-actin complex (Coué et al, 1987). The latrunculins have been used to inhibit actin function in a wide variety of systems, including animals (Spector et al, 1989), fungi (Ayscough et al, 1997;Gupta and Heath, 1997), and brown algae (Love et al, 1997;Hable and Kropf, 1998). Currently, few reports have been published on the effects of latrunculins on angiosperms (Bibikova et al, 1999;Zonia et al, 1999) and none on the interaction of latrunculin B (LATB) with actin from any organism in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Oospheres are initially spherical with no detectable polarity (Jaffe, 1958). After fertilisation (AF) Fucus zygotes deposit a cell wall within minutes and establish an axis of polarity in response to external cues (such as unidirectional light) that becomes fixed in space (14-18 hours AF) and leads to the germination of a rhizoid at the side facing away from the incident light (16-20 hours AF) (Henry et al, 1996;Love et al, 1997;Novotny and Forman, 1974). Concomitantly zygotes progress through the first cell cycle and divide perpendicularly to the growth axis (Corellou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%